Risk Factors for Postpartum Depression and Severe Distress among Mothers of Very Preterm Infants at NICU Discharge - Hofheimer, Julie A.; McGowan, Elisabeth C.; Smith, Lynne M.; Meltzer-Brody, Samantha; Carter, Brian S.; Dansereau, Lynne M.; Pastyrnak, Steven; Helderman, Jennifer B.; Neal, Charles R.; DellaGrotta, Sheri A.; O'Shea, Thomas Michael D.; Lester, Barry M. (American Journal of Perinatology, 2023)
Objective To identify psychological, medical, and socioenvironmental risk factors for maternal postpartum depression (PPD) and severe psychological distress (SPD) at intensive care nursery discharge among mothers of very preterm infants.Study Design We studied 562 self-identified mothers of 641 infants born <30 weeks who were enrolled in the Neonatal Neurobehavior and Outcomes in Very Preterm Infants Study (NOVI) conducted in nine university-affiliated intensive care nurseries. Enrollment interviews collected socioenvironmental data, depression, and anxiety diagnoses prior to and during the study pregnancy. Standardized medical record reviews ascertained prenatal substance use, maternal and neonatal medical complications. The Edinburgh Postnatal Depression Scale and Brief Symptom Inventory were administered at nursery discharge to screen for PPD and SPD symptoms, respectively.Results Unadjusted analyses indicated mothers with positive screens for depression (n = 76, 13.5%) or severe distress (n = 102, 18.1%) had more prevalent prepregnancy/prenatal depression/anxiety, and their infants were born at younger gestational ages, with more prevalent bronchopulmonary dysplasia, and discharge after 40 weeks postmenstrual age. In multivariable analyses, prior depression or anxiety was associated with positive screens for PPD (risk ratio [RR]: 1.6, 95% confidence interval [CI]: 1.1–2.2) and severe distress (RR: 1.6, 95% CI: 1.1–2.2). Mothers of male infants had more prevalent depression risk (RR: 1.7, 95% CI: 1.1–2.4), and prenatal marijuana use was associated with severe distress risk (RR: 1.9, 95% CI: 1.1–2.9). Socioenvironmental and obstetric adversities were not significant after accounting for prior depression/anxiety, marijuana use, and infant medical complications.Conclusion Among mothers of very preterm newborns, these multicenter findings extend others' previous work by identifying additional indicators of risk for PPD and SPD associated with a history of depression, anxiety, prenatal marijuana use, and severe neonatal illness. Findings could inform designs for continuous screening and targeted interventions for PPD and distress risk indicators from the preconception period onward.Key Points
Keywords: postpartum depression; severe psychological distress; prenatal marijuana use; very preterm infants